By Reverence, Not Fear: Prestige, Religion, and Autonomic Regulation in the Evolution of Cooperation - Lenfesty, Hillary L.; Morgan, Thomas J. H. (Frontiers in Psychology, 2019)
Recent evolutionary theories of the emergence of religions emphasize their function as mechanisms for increasing prosociality. They argue that this is necessary because third-parties (i.e., centralized authorities) are often unable to monitor behavior and mete out punishment in large groups. Moreover, they assert that deities operate most effectively when they are feared, as fear of supernatural punishment functions to inhibit anti-social behavior. Nonetheless, while fear of punishment may inhibit anti-social behavior, it is unlikely to motivate other prosocial behaviors. This is because human physiology has evolved separate neurological systems with differential behavioral correlates either for 1) processing fear and responding to threats or 2) facilitating communication in social interactions which are deemed safe. Almost all vertebrates possess autonomic pathways for processing threats and fear, which result in “fight”, “flight” or “freeze” responses and so likely mediate interactions in dominance hierarchies. Mammals, however, possess an additional, phylogenetically newer, pathway dedicated to suppressing such defensive responses in the service of promoting social affiliation or engagement. Here, we argue that this mammalian physiology supports an alternative hierarchical system unique to humans: prestige. In contrast to dominance, which involves aversion, fear and shame, prestige hierarchies are characterized by eye-contact and physical proximity, as well as emotions like awe and respect. Prestige also directs the flow of cultural information between individuals and has been argued to have evolved in order to help individuals acquire high quality information. Here, we argue that not only does the mammalian autonomic pathway support prestige hierarchies, but that coupled with prestige biased social learning, it opens up a means for prestigious figures, including deities, to support the spread of prosocial behaviors. Thus, contrary to theories that emphasizes religious fear as a motivating factor in the evolution of prosocial religions, we suggest that reverence – which includes awe and respect for, deference to, admiration of, and a desire to please a deity or supernatural agent – is likely just as important. In support of this, we identify historical cases of growth in religious groups that appear to be defined by prestige dynamics, and not fear of supernatural punishment.